The enteric nervous system in patients with calculous and acalculous gallbladder - Villanacci, Vincenzo; Del Sordo, Rachele; Salemme, Marianna; Cadei, Moris; Sidoni, Angelo; Bassotti, Gabrio (Digestive and liver disease, 2016)
It is generally thought that gallbladder motility plays a more or less important role in the pathogenesis of gallstones. Some studies have shown that some abnormalities of its intrinsic innervations, but these studies were usually limited to one cell component. We investigated the main cell components of gallbladder intrinsic innervation in patients with and without gallstones. Archival gallbladder specimens from 39 patients, 27 with gallstones (age range 45–69 yrs) and 12 patients without gallstones (age range 39–71 yrs) were obtained. Full thickness sections were obtained from the gallbladder neck and immunohistochemistry was carried out for enteric neurons (neuron-specific enolase and calretinin), enteric glia (S100) and interstitial cells of Cajal (CD117 and CD34); tryptase staining was also done to distinguish the latter from mast cells. Apart from calretinin-positive neurons, patients with gallstones featured a significant decrease of neurons, enteric glial cells (EGC) and mast cells compared to those without gallstones; interstitial cells of Cajal were extremely few and only found in two patients, one for each group. The intrinsic innervations of the gallbladder is abnormal in gallstone patients, and this may contribute to gallstone formation in these subjects.